Madrasah Teachers' Readiness in Developing Collaborative English Teaching Module - Safriyani, Rizka; Asmiyah, Siti (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2024)
This qualitative case study examines the readiness of five Madrasas to develop collaborative English teaching modules within an independent curriculum framework. These Madrasas were selected for their exemplary practices and potential to serve as models. Through appreciative interviews and asset discovery, we assessed readiness in critical areas: working conditions, teacher-student relationships, teacher qualifications, ICT readiness, and in-service training. The findings reveal a positive work culture characterized by post-training knowledge dissemination and collaborative learning plan sharing. Teacher-student solid relationships further support academic success, as demonstrated by student achievements in various competitions. Teacher qualifications are robust, with many possessing advanced degrees and engaging in continuous professional development. The readiness of these Madrasas is underscored by their ability to leverage past experiences, such as those from the USAID PRIORITAS initiative. The study highlights the significant readiness of these Madrasas to develop and implement independent curriculum teaching modules.